2018
DOI: 10.1542/peds.2018-1092
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding and Weight Gain: Separating Breast Milk From Breastfeeding and Formula From Food

Abstract: on behalf of the CHILD Study Investigators OBJECTIVES: Studies addressing breastfeeding and obesity rarely document the method of breast milk feeding, type of supplementation, or feeding in hospital. We investigated these practices in the CHILD birth cohort. METHODS: Feeding was reported by mothers and documented from hospital records. Weight and BMI z scores (BMIzs) were measured at 12 months. Analyses controlled for maternal BMI and other confounders. RESULTS: Among 2553 mother-infant dyads, 97% initiated br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
138
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 30 publications
(31 reference statements)
6
138
2
3
Order By: Relevance
“…As far as we know, limited Canadian data are available on breast pump practices in general. However, among 2,870 children in the Canadian Healthy Infant Longitudinal Development study, 57% of those who were breastfed at 3 months of age also received pumped breast milk (Azad et al, ). Our study participants used breast pumps for a range of reasons also identified in the literature: to maintain milk supply, to provide breast milk during breastfeeding problems, and to increase flexibility and allow others to help with infant feeding (Chamberlain, McMahon, Phillip, & Merewood, ; Labiner‐Wolfe et al, ; Win, Binns, Zhao, Scott, & Oddy, ).…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, limited Canadian data are available on breast pump practices in general. However, among 2,870 children in the Canadian Healthy Infant Longitudinal Development study, 57% of those who were breastfed at 3 months of age also received pumped breast milk (Azad et al, ). Our study participants used breast pumps for a range of reasons also identified in the literature: to maintain milk supply, to provide breast milk during breastfeeding problems, and to increase flexibility and allow others to help with infant feeding (Chamberlain, McMahon, Phillip, & Merewood, ; Labiner‐Wolfe et al, ; Win, Binns, Zhao, Scott, & Oddy, ).…”
Section: Discussionmentioning
confidence: 99%
“…With a growing body of evidence that feeding expressed breast milk might be different from feeding at the breast, this is an important finding. Studies have found that there is higher risk of asthma (17)and childhood obesity (18)(19)(20)with expressed breast milk feeding compared to direct breastfeeding. There are also concerns that only feeding expressed breastmilk could result in shorter duration of breastfeeding (20).In our study,expressed breastfeeding in the first month of life did not make any difference to our 6-month breastfeeding rates, but our study was not designed to answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…31 Breastfeeding is crucial in early childhood and continues to show beneficial effects for preventing childhood obesity. 103 Breastfed infants exhibited different gut microbiota and SCFA concentrations compared to formula-fed infants. 41 Infant formula supplemented with GOS increased Bifidobacteria and Lactobacillus levels in human infants similar to those of breastfed infants.…”
Section: Probiotics and Prebiotic Effects Of Breastmilk And Breastfmentioning
confidence: 99%
“…Newborn mice supplemented with a synbiotic of GOS and Bifibacterium breve showed decreased body weight and improved insulin sensitivity and lipid profile while being fed an HFD‐diet throughout life . Breastfeeding is crucial in early childhood and continues to show beneficial effects for preventing childhood obesity . Breastfed infants exhibited different gut microbiota and SCFA concentrations compared to formula‐fed infants .…”
Section: Probiotics Prebiotics and Obesitymentioning
confidence: 99%